2006
DOI: 10.3354/meps319135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food availability on sediment reworking in Abra ovata and A. nitida*

Abstract: We used a new experimental approach involving thin aquaria, luminophores, time lapse photography and image analysis to assess sediment reworking in 2 closely related bivalves, Abra ovata and A. nitida. The method proved efficient based on the highly significant correlation between the concentrations of luminophores assessed using image analysis and direct counting of sediment slices. A. ovata and A. nitida exhibited different sediment reworking behaviours. A. ovata remained immobile within the sediment and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 45 publications
2
77
0
2
Order By: Relevance
“…Increasing food availability can increase foraging activity by benthic animals (Jumars and Wheatcroft 1989;Maire et al 2006), which can aVect sediment proWles of pigments and other constituents. Moreover, chl a:phaeo ratios can be used as indicators of the degradation of organic matter (Boon and Duineveld 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing food availability can increase foraging activity by benthic animals (Jumars and Wheatcroft 1989;Maire et al 2006), which can aVect sediment proWles of pigments and other constituents. Moreover, chl a:phaeo ratios can be used as indicators of the degradation of organic matter (Boon and Duineveld 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the addition of low concentrations of organic matter significantly enhanced the feeding activity of this bivalve. In sediment column experiments using thin aquaria, and the same techniques with Abra ovata, a low organic input also induced a significant increase of vertical sediment mixing (Maire et al 2006), suggesting a positive relationship between the intensity of feeding activity and vertical sediment mixing. However, these measurements were not made simultaneously, since activity was measured at the sediment surface whereas sediment mixing was measured within the sediment column.…”
Section: Introductionmentioning
confidence: 97%
“…Through these ecological processes, the infauna has an impact on oxygen uptake (Andersen & Kristensen 1988, Glud et al 2003, porewater fluxes (Marinelli 1992(Marinelli , 1994, and sediment reworking (Rhoads 1974, Aller 1982. The resulting effects are clearly dependent on the nature and the intensity of infaunal activity (Boudreau & Marinelli 1994, Gérino et al 1998, Maire et al 2006.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations